Developing Metadata Application Profiles for Open Educational Resources Federated Repositories: The Case of the Open Discovery Space Metadata Application Profile - Zervas, P.; Sampson, Demetrios (2017)
With many Learning Object Repositories (LORs) implemented and maintained independently from different organizations or communities, valuable Learning Objects (LOs) are scattered over different LORs and making it difficult for end-users (namely, instructional designers, teachers and students) to easily find and access them. A suggested solution towards addressing this issue is to create federated LORs, which aim to harvest and aggregate LOs' metadata from different LORs towards facilitating LOs' discovery across these LORs through a single infrastructure. However, a challenging issue during the development of federated LORs is the design of appropriate metadata application profile (AP) which supports harvesting heterogeneous metadata records from the aggregated LORs. Thus, the aim of this book chapter is twofold, namely (a) to present a methodology for developing metadata APs that can be used in building federated LORs and (b) to present a case study from the implementation of the proposed methodology for the development of the metadata AP used by the OpenDiscoverySpace federated LOR.